Experimental study of lifetimes of excited states in the Kπ = 0− octupole band and γ-vibrational band in 228Th. (December 2020) - Chishti, M.M.R.; O'Donnell, D.; Battaglia, G.; Bowry, M.; Jaroszynski, D.A.; Singh, B.S. Nara; Scheck, M.; Spagnoletti, P.; Smith, J. F.
Abstract: Lifetimes of excited states in the K π = 0 − octupole band and γ -vibrational of 228 Th have been measured using the fast timing setup at the University of the West of Scotland (UWS). The setup consists of two cerium doped LaBr3 fast scintillators placed equidistant from the radioactive source 232 Th. The states of interest have been analysed by doing the triple γ – γ – time coincidence analysis and using the fast-timing technique, mirror-symmetric centroid difference method. Octupole collectivity in 228 Th nucleus is also investigated by calculating the enhanced electric dipole moments and transition rates in excited states followed by lifetime measurements in octupole band.